Upaya Meningkatkan Karakter Disiplin Anak Melalui Pohon Kedisiplinan di Tk IK Keluarga Ceria Sleman - Rizqiyyatunnisa Rizqiyyatunnisa (Jurnal Pendidikan Raudhatul Athfal, 2020)
The background of the problem in this study is that the behavior of the discipline is not fully owned by the children, so that it affects the teaching and learning process in the classroom. There needs to be a renewal in the form of strategies or media that can familiarize the discipline behavior of children, so that children can get used to discipline by using the discipline tree. This study aims to determine the application of the "Disciplinary Tree" in improving the character of child discipline and to measure the increase in the character of child discipline through "Disciplinary Trees in Kindergarten IK Ceria Family Sleman. The research method used is a research method with a qualitative approach in the form of classroom action research (CAR). Data collection is done by observation, interviews, and documentation. The subjects in this study were children of Class B1 Kindergarten IK IK Ceria Sleman Family with a total of 22 students, consisting of 9 girls and 13 boys. The results of this study can be concluded that: 1) the application of the discipline tree is done by introducing the discipline tree, its function and how to use it in children, then the children are asked to try and apply it during the learning activities. The teacher observes the child's disciplined attitude when using the discipline tree; 2) increasing the character of child discipline through Disciplinary Trees at IK IK Ceria Happy Family by 39.7%